The Lesson of Things: Halina Grynberg and the Post-Shoah Jewish Literature in Brazil - Nascimento, Lyslei (Women in Judaism, 2023)
The poem “As coisas têm alma” by Maria José de Queiroz (1934-2023), and the book Lição de Coisas by Carlos Drummond de Andrade (1902-1987), illuminate the reading of Mameloshn: memória em carne viva (2004) and O padeiro polonês (2015) by Halina Grynberg. The eleven-year time that separates the two novels does not make their reading more palatable. On the contrary, the doubling of the number 1 (one) points symbolically to the double condition of the narratives. In both, “the memory in the flesh” translates to “the violence of being a survivor,” as stated by Nilton Bonder (2004). The Holocaust, he adds, generates cruelty, exile from one’s homeland and, mainly, exile from human territory, humans’ most primitive language. In this sense, the things or items referenced, cited or listed bring into play objects and things that are part of a ruined world that is mobilized through memory by writers and narrators.